TPR (Total Physical Response) Untuk Meningkatkan Gerak Lokomotor Anak Usia 5-6 Tahun - Pratiwi, Warih Anggi; Prehatiningsih, Arip (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
This study aims to determine the effectiveness of the Total Physical Response (TPR) method in improving the locomotor movement skills of children aged 5–6 years in kindergarten. Locomotor movement is a part of gross motor development essential in supporting children's physical activities, such as walking, running, jumping, and hopping. However, initial observations showed that most children still experienced difficulty performing locomotor movements properly. Therefore, a learning approach that can stimulate motor skills in a fun and meaningful way is needed. The TPR method was chosen because it combines verbal instructions with active physical responses, which aligns with the developmental characteristics of early childhood who enjoy learning through movement and play. This research employed a classroom action research (CAR) approach using the Kemmis and McTaggart model, consisting of two cycles. Data collection techniques included observation and documentation, while the instrument used was a locomotor movement assessment sheet based on six main indicators: walking in a straight line, running, jumping, hopping, stair climbing, and crawling. The research subjects were 20 children in Group B (aged 5–6 years) at BA Aisyiyah Rejosari in Sukoharjo Regency. The results of the study showed a significant improvement in locomotor movement skills from cycle to cycle. The average locomotor movement scores of the children increased from the pre-action stage (30.55%), to Cycle I (76.55%), and then to Cycle II (87.78%). This improvement indicates that the TPR method is effective in stimulating children’s fundamental movements actively and enjoyably. Additionally, the children demonstrated increased motivation and enthusiasm throughout the activities. Thus, the TPR method can be considered an appropriate alternative strategy for gross motor learning in the context of early childhood education.